2020
DOI: 10.1038/s41598-020-63337-5
|View full text |Cite
|
Sign up to set email alerts
|

First interchromosomal insertion in a patient with cerebral and spinal cavernous malformations

Abstract: Autosomal dominant cerebral cavernous malformations (ccM) are leaky vascular lesions that can cause epileptic seizures and stroke-like symptoms. Germline mutations in either CCM1, CCM2 or CCM3 are found in the majority of patients with multiple CCMs or a positive family history. Recently, the first copy number neutral inversion in CCM2 has been identified by whole genome sequencing in an apparently mutation-negative CCM family. We here asked the question whether further structural genomic rearrangements can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Nonetheless, no causative variant is identified in 2%–13% of familial CCM cases by current genetic analyses ( Spiegler et al, 2018b ). Apart from structural variants ( Spiegler et al, 2018a ; Pilz et al, 2020 ) and somatic mosaicism ( McDonald et al, 2014 ), the here identified CCM1 TSS deletion highlights that variants in regulatory regions that are not always analyzed in routine diagnostics may account for part of the missing heritability in CCM disease.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, no causative variant is identified in 2%–13% of familial CCM cases by current genetic analyses ( Spiegler et al, 2018b ). Apart from structural variants ( Spiegler et al, 2018a ; Pilz et al, 2020 ) and somatic mosaicism ( McDonald et al, 2014 ), the here identified CCM1 TSS deletion highlights that variants in regulatory regions that are not always analyzed in routine diagnostics may account for part of the missing heritability in CCM disease.…”
Section: Discussionmentioning
confidence: 90%
“…The detection of complex SVs is hard or even impossible with short-read gene panel sequencing. Since the identification of an interchromosomal insertion and an inversion in CCM2 [ 8 , 9 ] suggests that SVs must be considered as a possible cause of familial CCM disease, we wanted to test whether long-read sequencing could accurately detect these variants. Therefore, we reanalyzed a heterozygous 24 kb inversion on chromosome 7 ( Figure 4 a), which covers the first coding exon of CCM2 [ 8 ], with long-read sequencing ( Figure 4 b; Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the next step, we re-analyzed a known heterozygous interchromosomal insertion of chromosome 1 material into the coding region of CCM2 ( Figure 5 a). This variant which we had previously called from short read gene panel sequencing data with the SureCall software, was an ideal positive control for our approach because it already had been extensively characterized and confirmed by FISH [ 9 ]. Long-read sequencing of DNA with this variant ( Table S3 ) generated single reads longer than 20 kb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of spinal cord-related neurovascular diseases and other pathological processes are associated with vascular alterations (Wu et al, 2008 ; Heldner et al, 2012 ). Such as the cavernous hemangiomas in the spinal cord consist of abnormal blood vessels with poor blood flow (Pilz et al, 2020 ). The spinal dural arteriovenous (AV) fistulas are the most commonly encountered vascular malformation of the spinal cord and still underdiagnosed entities (Takai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%